Effects of hydrographic conditions on the transport of neon flying squid Ommastrephes bartramii larvae in the North Pacific Ocean - Kato, Yoshiki; Sakai, Mitsuo; Mmasujima, Masachika; Okazak, Makoto; Igarashi, Hiromichi; Masuda, Shuhei; Awaji, Toshiyuki (HIDROBIOLÓGICA, 2016)
The neon flying squid, Ommastrephes bartramii, is widespread in subtropical and temperate regions. In the North Pacific Ocean, the species is comprised of two spawning cohorts; an autumn cohort and a winter-spring cohort. Interestingly, despite their apparently contiguous hatching periods, there is a marked disparity in the mantle length of both cohorts. We hypothesized that differences in the ambient temperature during larval development were responsible for the observed disparity in mantle size. Numerical simulations of ambient temperature revealed that water temperatures were approximately 1 °C higher in areas inhabited by the autumn cohort than they were in areas inhabited by the winter-spring cohort. The findings imply that differences in ambient water temperature and nutrient condition may be responsible for the observed differences in the growth of the autumn and winter-spring cohorts.